Randomized trial of a novel lifestyle intervention compared with the Diabetes Prevention Program for weight loss in adult dependents of military service members. Issue 4 (10th August 2021) - Das, Sai Krupa; Bukhari, Asma S; Taetzsch, Amy G; Ernst, Amy K; Rogers, Gail T; Gilhooly, Cheryl H; Hatch-McChesney, Adrienne; Blanchard, Caroline M; Livingston, Kara A; Silver, Rachel E; Martin, Edward; McGraw, Susan M; et al.
ABSTRACT: Background: Lifestyle interventions are the first-line treatment for obesity, but participant weight loss is typically low. Objectives: We evaluated the efficacy of an alternative lifestyle intervention [Healthy Weight for Living (HWL)] compared with a modified Diabetes Prevention Program (m-DPP). HWL was based on a revised health behavior change model emphasizing hunger management and the development of healthy food preferences. m-DPP was a standard Diabetes Prevention Program implemented with counselor time matched to HWL. Participants were adult dependents of military personnel and had overweight or obesity. Methods: Participants were randomly assigned to HWL ( n  = 121) or m-DPP ( n  = 117), delivered primarily by group videoconference with additional midweek emails. The primary outcome was 12-mo weight change. Secondary outcomes included 6-mo changes in cardiometabolic risk factors and diet. Intention-to-treat (ITT) and complete case (CC) analyses were performed using linear mixed models. Results: Retention did not differ between groups (72% and 66% for HWL and m-DPP at 12 mo, respectively; P  = 0.30). Mean ± SE adjusted 12-mo weight loss in the ITT cohort was 7.46 ± 0.85 kg for HWL and 7.32 ± 0.87 kg for m-DPP ( P  = 0.91); in the CC cohort, it was 7.83 ± 0.82 kg for HWL and 6.86 ± 0.88 kg for m-DPP ( P  = 0.43). Thirty-eight percent of HWL and 30% of m-DPP completers achieved ≥10% weight loss ( P  = 0.32). Improvements in systolic blood pressure, LDL cholesterol, triglycerides, fasting glucose, general health, sleep, and mood were similar across groups; improvements in diastolic blood pressure were greater in m-DPP. Adjusted group mean reductions in energy intake were not significantly different between groups, but HWL participants were more adherent to their dietary prescription for lower glycemic index and high fiber and protein ( P  = 0.05 to <0.001 for ITT). Conclusions: HWL and m-DPP showed equivalent and clinically impactful mean weight loss with cardiometabolic benefits. These results identify an alternative approach for behavioral treatment of overweight and obesity. This trial was registered at clinicaltrials.gov as NCT02348853.